2006
DOI: 10.1007/s00125-006-0520-0
|View full text |Cite
|
Sign up to set email alerts
|

Exercise under hyperinsulinaemic conditions increases whole-body glucose disposal without affecting muscle glycogen utilisation in type 1 diabetes

Abstract: Aims/hypothesis We examined whole-body and muscle metabolism in patients with type 1 diabetes during moderate exercise at differing circulating insulin concentrations. Methods Eight men (mean±SEM age 36.4±1.5 years; diabetes duration 11.3±1.4 years; BMI 24.6±0.7 kg/m 2 ; HbA 1c 7.9±0.2% and VO 2 peak 44.5±1.2 ml kg −1 min −1 ) with type 1 diabetes were studied on two occasions at rest (2 h) and during 45 min of cycling at 60% maximum VO 2 with insulin infused at the rate of either 15 (LO study) or 50 (HI) mU m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…Regarding the studies included here, three articles [28,31,33] did not provide experimental data on insulin concentration. In the following three cases, patients exercised at levels lower than both conditions in Chokkalingam et al [52]: Jankovec et al [32] (average insulinemia ~ 80 pmol/L and great inter-subject variability, without statistical differences versus REST); Soo et al [36] (basal 84 ± 18 pmol/L, mean ± SEM; authors reported no significant correlation between basal free insulin and glycemic response); and Yamanouchi et al [37] (pre-prandial trial arm [55.3 ± 21.5 pmol/L, mean ± SD]). Peter et al [34] documented an average plasma insulin of ~ 300 pmol/L during both REST and CONT, without statistical differences between trials in terms of area under the curve for insulinemia (p -0.116).…”
Section: Strengths and Limitationsmentioning
confidence: 86%
See 3 more Smart Citations
“…Regarding the studies included here, three articles [28,31,33] did not provide experimental data on insulin concentration. In the following three cases, patients exercised at levels lower than both conditions in Chokkalingam et al [52]: Jankovec et al [32] (average insulinemia ~ 80 pmol/L and great inter-subject variability, without statistical differences versus REST); Soo et al [36] (basal 84 ± 18 pmol/L, mean ± SEM; authors reported no significant correlation between basal free insulin and glycemic response); and Yamanouchi et al [37] (pre-prandial trial arm [55.3 ± 21.5 pmol/L, mean ± SD]). Peter et al [34] documented an average plasma insulin of ~ 300 pmol/L during both REST and CONT, without statistical differences between trials in terms of area under the curve for insulinemia (p -0.116).…”
Section: Strengths and Limitationsmentioning
confidence: 86%
“…However, the amount of muscle glycogen utilized in both situations was similar, and carbohydrate oxidation rates were only around 15 % more in the trial arm with the highest insulinemia. Consequently, the influence of distinct plasma insulin levels in otherwise equivalent exercise conditions remains unclear, as outlined by Chokkalingam et al [52]. Regarding the studies included here, three articles [28,31,33] did not provide experimental data on insulin concentration.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…The impact of real-life therapeutic insulin concentrations on hepatic glycogen metabolism during exercise in patients with type 1 diabetes is not known. We have recently shown that, in patients with type 1 diabetes, exercise under peak therapeutic insulin concentrations increases exogenous glucose utilisation and that this increase is disproportionate to the relative increase in carbohydrate oxidation, suggesting an increase in glucose flux through non-oxidative pathways, perhaps towards hepatic glycogenesis [25].…”
Section: Introductionmentioning
confidence: 99%